Strategi Komunikasi Desa Kedang Murung Dalam Pengembangan Objek Wisata Tanjung Sarai - Muhammad Ramadhani Julistia; Kadek Dristiana Dwivayani; Ainun Ni'Matu Rohmah; Dony Kristian (Lembaga Dongan Dosen, 2025)
This thesis discusses communication strategies which are an approach used to convey information, persuade and remind consumers about a promotion either directly or through the media. The aim of this research is to find out the communication strategy of Kedang Murung Village in developing the Tanjung Sarai tourist attraction. The research method used is qualitative with a descriptive approach, and data is collected through interviews, observation and documentation. The informants involved the village head, BumDes chairman and visitors. The research results show that the communication strategy for developing the Tanjung Sarai Lake tourist attraction uses all of Hafied Cangara's theories, namely, the selection of communicators involves a lot of the role of Bumdes and young people. In determining the target, the focus is local tourists. Then, in preparing the message, the themes raised were the authenticity of nature, the beauty of the panorama and the richness of local culture. The choice of media used is social media such as Instagram, TikTok and Facebook.